Adaptation and validation of the patient assessment of chronic illness care in United States community pharmacies - Omolola A. Adeoye-Olatunde; Naomi Pratt; David D. Kim; Evan Schmidt; Margie E. Snyder (BMC, 2022)
Abstract Background Roles for United States (US)-based community pharmacists in caring for persons with chronic conditions have greatly expanded. The Patient Assessment of Chronic Illness Care (PACIC) was developed to assess patients' perspectives of care received. However, successful application of this instrument in community pharmacies is uncertain. The objective of this study was to adapt the PACIC for use in community pharmacies (CP-PACIC), assess validity of the CP-PACIC and examine CP-PACIC scale score differences relative to patient characteristics. Methods This cross-sectional study surveyed chronically ill adults in Indiana, US who receive care from pharmacists in community pharmacies. The modified CP-PACIC scale consisted of 20-items, which were rated on a 5-point Likert scale from 0 (none of the time) to 4 (always). The total possible score ranged from 0 - 80. An exploratory factor analysis (EFA) was conducted to assess performance and dimensionality. CP-PACIC validity, including face validity, construct validity (via exploratory factor analysis) and internal consistency were assessed. Relationships between patient characteristics and scale scores were evaluated using appropriate statistical tests. Results Five hundred forty-six respondents' data were analyzed. EFA revealed a 2-factor solution (termed advanced pharmacy chronic illness care (AP) and traditional pharmacy chronic illness care (TP) subscales) accounting for 64.7% of variance; all 20 items were retained. The total 20-item CP-PACIC scale had a Cronbach's alpha (internal consistency) of 0.96; with a 12-item AP subscale Cronbach's alpha of 0.97 and 8-item TP subscale Cronbach's alpha of 0.89. Median total score was 12.0 [interquartile range = 27.3]. Median CP-PACIC sores varied across many respondent demographics (i.e., survey administration type, age, sex, education, health condition, number of pharmacy services received, community pharmacy type) such as whether respondents participated in one or more pharmacy service or not (29 vs. 10; p < .001). Conclusions Unlike the original 5-subscale (patient activation, delivery system design, goal setting, problem solving, and follow-up/coordination) PACIC, analysis demonstrated a 2-factor (AP, TP) solution for the CP-PACIC scale with good internal consistency. As there are no standardized evaluation tools that exist, community pharmacies could find great value in using this CP-PACIC tool to benchmark performance and inform quality improvement strategies for patient care delivery.